Mploy - a Job Readiness Workbook : Career Skills Development for Young Adults on the Autism Spectrum and with Learning Difficulties. - McManmon, Michael P. (Jessica Kingsley Publishers, 2017)
This ready-to-use workbook provides everything you need to help young people with autism or learning differences prepare for work. Suitable for those working with young adults aged 16-26, this workbook includes activities and worksheets designed to develop key skills for meaningful careers, so young people can enter employment with confidence.